The Headmaster’s Strategy in Improving Teachers’ Professionalism at MI Muhammadiyah Srebegan - Nugroho, Joko Agung; Anshori, Ari; Jinan, Mutohharun (Interdisciplinary Social Studies, 2022)
Background: The Head of a Madrasah is the leader of education unit level education, which must be responsible for all Madrasah activities. In addition, the Head of Madrasah is an education leader whose position is very important in the Madrasah environment because the Head of Madrasah is more closely and directly related to the implementation of each educational program. Aim: Revealing the strategy of the Head of MI Muhammadiyah Srebegan in improving the professionalism of the teachers Method: Fieldwork is used in this study. A descriptive analysis using inductive thinking was employed as the method. Meanwhile, this research relies on observation, interviews, and documents to get the necessary information. Findings: The Head of Madrasah’s strategy for developing teacher professionalism at MI Muhammadiyah Srebegan starts with defining Madrasah's vision, mission, and goals. Madrasah's external and internal environments are observed during the procedure. The final step in the strategy development process for the head of MI Muhammadiyah Srebegan was to formulate the Madrasah plan, which is included in the Madrasah Work Program, which is prepared once a year at the start of the school year.